2013
DOI: 10.1186/1472-6920-13-77
|View full text |Cite
|
Sign up to set email alerts
|

Effective or just practical? An evaluation of an online postgraduate module on evidence-based medicine (EBM)

Abstract: BackgroundTeaching the steps of evidence-based medicine (EBM) to undergraduate as well as postgraduate health care professionals is crucial for implementation of effective, beneficial health care practices and abandonment of ineffective, harmful ones. Stellenbosch University in Cape Town, South Africa, offers a 12-week, completely online module on EBM within the Family Medicine division, to medical specialists in their first year of training. The aim of this study was to formatively evaluate this module; asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Recent years have seen a surge in the number of online courses offered to healthcare professionals. Courses being offered online come with the advantage of offering clinicians more flexibility in reaching their continued professional development goals and have been reported as successfully leading to improvements in both knowledge and skill (Bello et al, 2005;Hopper & Johns, 2007;Hugenholtz et al, 2008;Rohwer et al, 2013). This paper details the expectations, concerns, and experience of 19 students enrolled on an online postgraduate certificate in Clinical Exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent years have seen a surge in the number of online courses offered to healthcare professionals. Courses being offered online come with the advantage of offering clinicians more flexibility in reaching their continued professional development goals and have been reported as successfully leading to improvements in both knowledge and skill (Bello et al, 2005;Hopper & Johns, 2007;Hugenholtz et al, 2008;Rohwer et al, 2013). This paper details the expectations, concerns, and experience of 19 students enrolled on an online postgraduate certificate in Clinical Exercise.…”
Section: Discussionmentioning
confidence: 99%
“…What is perhaps most interesting about the student expectations was that students expressed an expectation that the knowledge gained would lead to an improvement in their prescription skills. It has been shown that fully online courses imparting knowledge can lead to an improvement in clinician skills (Bello et al, 2005;Edrich et al, 2016;Rohwer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The five key competencies mirror the five steps of EBHC, namely i) formulating an answerable question based on clinical uncertainty; ii) finding the best available evidence to answer this question; iii) critically appraising and interpreting the evidence; iv) applying the results in the clinical setting; and v) evaluating the performance [3]. We discussed these proposed competencies with other faculty members and external experts before finalising them (Figure 1) [7].
Figure 1 Undergraduate enabling and key EBHC competencies.
…”
Section: Methodsmentioning
confidence: 99%
“…There has also been improved access to evidence through the HINARI initiative [24], and free one-click access to the Cochrane Library for people in many African countries. Furthermore, postgraduate and continuing professional development courses in EBHC are increasing whether measured in the number of programmes or the number of enrollees [25,26]. In 2012, the signing of the Kigali declaration on EBHC [27] by representatives from academe, hospitals, NGOs and research institutions from nine African countries, forming part of the Collaboration for Evidence based Health in Africa, signalled a key milestone in the recognition of EBHC and the momentum for moving towards the implementation of evidence based practices (Box).…”
Section: A N U S C R I P Tmentioning
confidence: 99%